2016
DOI: 10.1515/ctra-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

Slumps and Jumps: Another Look at Developmental Changes in Creative Abilities

Abstract: The aim of this study is the analysis of creativity changes across life, particularly the widely discussed crisis periods in the development of creative abilities. A large and diversified sample of Poles (N = 4898 aged from 4 to 21 years), at each educational stage of the Polish education system, from pre-schoolers, through primary school students, middle-school students, secondary-school students and finally university students completed the Test for Creative Thinking – Drawing Production. The observed change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 59 publications
3
35
0
3
Order By: Relevance
“…The development of DT in children has been a well-studied topic in the field of education for more than fifty years ( Smith and Carlsson 1985 ; Kim 2011 ). However, the empirical findings regarding children’s creativity have not been consistent in the literature ( Gralewski et al 2017 ; Said-Metwaly et al 2020 ). For pre-schooled children (2 years old) ( Bijvoet-van den Berg and Hoicka 2014 ), the individual differences in DT performances seem to increase across grade levels (e.g., Sak and Maker 2006 ), and tend to continue until about age 40, followed by a “systematic maturational declines” ( McCrae et al 1987 ).…”
Section: Introductionmentioning
confidence: 75%
“…The development of DT in children has been a well-studied topic in the field of education for more than fifty years ( Smith and Carlsson 1985 ; Kim 2011 ). However, the empirical findings regarding children’s creativity have not been consistent in the literature ( Gralewski et al 2017 ; Said-Metwaly et al 2020 ). For pre-schooled children (2 years old) ( Bijvoet-van den Berg and Hoicka 2014 ), the individual differences in DT performances seem to increase across grade levels (e.g., Sak and Maker 2006 ), and tend to continue until about age 40, followed by a “systematic maturational declines” ( McCrae et al 1987 ).…”
Section: Introductionmentioning
confidence: 75%
“…It is also broadly consistent with the work of Kleibeuker et al (2013) who found no differences in fluency across four age groups, 12/13, 15/16, 18/19 and 25-30, although they did find a difference in originality between their 12/13 and 15/16 groups and the young adult 25-30 group. Other studies which used the Test for Creative Thinking -Drawing Production (TCT-DP; Urban, 2005) found a dip in creativity during adolescence (Gralewski et al, 2016;Jastrzębska & Limont, 2017), which was not seen here in the verbal divergent thinking task. Wu et al (2005) suggested that the level of knowledge and language ability required for the AUT may not differentiate the two groups in their study, and Kleibeuker et al (2013) suggested that the ability to generate multiple ideas is fully developed by early adolescence.…”
Section: Discussionmentioning
confidence: 47%
“…Divergent thinking develops intensively in late adolescence and emerging adulthood (Kleibeuker et al, 2013). This also applies to the more synthetic creative abilities as measured by the figural Test of Creative Thinking-Drawing Production (TCT-DP) (Urban, 2005); a large study observed an increase in results from adolescents to around 19 years of age, with a peak at 20 years of age and further stabilization at around age 21 (Gralewski et al, 2016).…”
Section: Changes In the Level Of Creative Abilitymentioning
confidence: 99%